1995
DOI: 10.1029/94jd02953
|View full text |Cite
|
Sign up to set email alerts
|

The use of NOy, H2O2, and HNO3 as indicators for ozone‐NOx‐hydrocarbon sensitivity in urban locations

Abstract: Correlations are presented between model predictions for O3‐NOx‐hydrocarbon sensitivity and afternoon concentrations of four “indicator species”: NOy, O3/(NOy‐NOx), HCHO/NOy, and H2O2/HNO3. The indicator species correlations are based on a series of photochemical simulations with varying rates of anthropogenic and biogenic emissions and meteorology. Hydrocarbon‐sensitive chemistry in models is shown to be linked to afternoon NOy > 20 ppb, O3/(NOy ‐ NOx) < 7, HCHO/NOy < 0.28, and H2O2/HNO3 < 0.4. Lower NOy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
513
2
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(564 citation statements)
references
References 31 publications
22
513
2
4
Order By: Relevance
“…Using an analysis of the ozone production efficiency and indicator variables (cf. also [Sillman, 1995]), they could show that ozone production in Verzago was rather ROG-sensitive in these cases.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Using an analysis of the ozone production efficiency and indicator variables (cf. also [Sillman, 1995]), they could show that ozone production in Verzago was rather ROG-sensitive in these cases.…”
Section: Methodsmentioning
confidence: 94%
“…Our interpretation is that ozone isopleth plots derived from measured values of ozone and it's precursors (reactivity weighted hydrocarbons (=ROGs) and either NOx or NOz) are suitable to identify the sensitivity of ozone production at one given site. In a previous paper [Thielmann et al, submitted], we analyzed the sensitivity of ozone production using the indicator variables introduced by [Sillman, 1995]. Indicator variables are derived from measured values of photochemical products.…”
Section: Discussionmentioning
confidence: 99%
“…[20] The daily OPE x in this study is always lower than the value suggested for O 3 -VOC sensitivity (OPE x < 7, [Sillman, 1995]), indicating that the ozone production in summer in Beijing is VOC-limited. Therefore, measures to control VOC emissions in Beijing would be effective to reduce O 3 levels.…”
Section: Ozone Production Efficiency (Ope X )mentioning
confidence: 96%
“…3. The comparison of the O•4NOy ratios to model simulations [Sillman, 1995] suggests that the rural and suburban locations are in a NOx -sensitive oxidant t•)nnation chemistry regime while the urban location (downtown Nashville) is in a chemistry regime that is sensitive to both NOx and VOC concentrations.…”
Section: Ozone Production Efficiency In Air Masses Impacted By Power mentioning
confidence: 99%